Prevalence of cardiac autonomic neuropathy in patients with type 2 diabetes mellitus - Aditya Karthikeyan; PR Manjunath; A Tharuni Latha; Sana Sultana (Journal of Family Medicine and Primary Care)
Introduction: Cardiac autonomic neuropathy (CAN) is one of the microvascular complications of diabetes mellitus, which is due to the involvement of autonomic nerve fibers innervating the heart and blood vessels. CAN was found to have a greater degree of morbidity and mortality than their non-CAN counterparts as it is underdiagnosed. Hence, this study aims to determine the prevalence and severity of CAN in type 2 diabetics in the South Indian setting. Materials and Methods: Forty-two patients with type 2 diabetes mellitus were enrolled in the study. Patients underwent tests for CAN, with the severity of CAN estimated as a CAN score, which was the sum of the scores of the four cardiovascular autonomic function tests. Results: Out of the 42 patients, a total of 36 patients (85.7%) were diagnosed with CAN. Among those with CAN, 24 patients had early CAN (57.1%), and 12 were diagnosed with definite CAN (28.6%). Patients with any form of CAN (early and definite CAN) had higher HbA1c and mean glucose values than those without CAN. CAN was also found to be more severe among older patients with diabetes. Conclusion: In the present study, we found that more than 50% of the study population had early CAN and around 28.6% patients had definite CAN indicating higher prevalence of CAN in our population. Also, there was a positive correlation between the severity of CAN and the age of the patients. This study highlights the importance of understanding the importance of screening the diabetic patients for CAN to prevent adverse cardiovascular events.